2013
DOI: 10.1055/s-0033-1337927
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of the New Potent Acetylcholinesterase Inhibitor 8-[3-[1-[(3-fluorophenyl)methyl]-4-piperidiny]-1-oxopropyl]-1, 2, 5, 6-tetrahydro-4H-pyrrolo [3, 2, 1-ij] quinolin-4-one (TAK-802) in Rats, Dogs and Monkeys

Abstract: The pharmacokinetics of TAK-802, a potential agent of amelioration for voiding dysfunction, were investigated in rats, dogs and monkeys after a single oral administration of 14C-labeled TAK-802. The values of the bioavailability for the compound ranged from 10.2 to 19.9% and the extent of absorption of 14C were higher than the values for the bioavailability in the tested animals. TAK-802 and its related compounds distributed widely in the tissues including the target organ, the urinary bladder, in rats. TAK-80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…dosing mainly depended on the concentration‐dependent erythrocyte distribution. In the erythrocyte distribution study using animals and human blood, the biggest concentration dependency of erythrocyte distribution was also confirmed in human at the tested concentration range . In the candidate selection stage, TAK‐802 exhibited high selectivity and potent inhibitory effects on AchE in an in vitro study using human erythrocyte‐derived acetylcholinesterase with an estimated IC 50 value of 1.5 nmol/l .…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…dosing mainly depended on the concentration‐dependent erythrocyte distribution. In the erythrocyte distribution study using animals and human blood, the biggest concentration dependency of erythrocyte distribution was also confirmed in human at the tested concentration range . In the candidate selection stage, TAK‐802 exhibited high selectivity and potent inhibitory effects on AchE in an in vitro study using human erythrocyte‐derived acetylcholinesterase with an estimated IC 50 value of 1.5 nmol/l .…”
Section: Discussionmentioning
confidence: 70%
“…The non‐clinical absorption, distribution, metabolism and excretion (ADME) data revealed that TAK‐802 exhibited a marked concentration‐dependency in the erythrocyte distribution in rats, dogs, monkeys and humans. The erythrocyte distribution changed from 77.0% to 11.5% in rats, 69.3% to 27.2% in dogs and 92.3% to 16.9% in monkeys at the tested concentration range of 1–1000 ng/ml . Especially in humans, the erythrocyte distribution changed significantly and ranged from 4.4% to 91.2% at the tested concentrations .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations